Bullying Experiment based on The Doers’ Perspective, Victim and Eye Witness on The Junior High School Student - Masruroh, Nurlailatul (Jurnal Keperawatan, 2016)
The Bullying Phenomena of 40 countries showed that Indonesia is ranked as the world's second highest state for bullying cases. The aim of this study is to provide an overview of Bullying Experience in Perspective Actors, Victims and Witnesses of The Junior Student "X" Batu City. The design and approach is Descriptive Qualitative and Case Study, it conducted in-depth semi-structured interviews to 11 participants consisting of students perpetrators, witnesses and victims of bullying. Data validation against other sources, those are the School Counseling unit and also Students`Family. In completing the data collection was also carried out observation and study documentation. Data collected was analyzed by using the Thematic Analysis, and the results are summarized into five themes, namely: (1) The Bullying Actorshave Academic Problems (2) Poor Social and Economic Background of Family of The Bullying Actors, (3) The Bullying action was Generally Conducted by Senior Students while the Victims were Junior, (4) The overall Bullying Actors are Male Students while the Victims are Female, (5) Activities included within Bullying are Physical, verbal and sexual harassment. It is also interesting to note that from all victims, factors and also the witness of bullying considered that bullying is something that should be avoided.